Empowering First Aiders Through Innovative Instructor Resources (International Journal of First Aid Education)
Provides an overview of how twice yearly first aid training days addressed instructor fatigue at the University of Calgary through supervisor observation and feedback while engaging in new, fun activities. Participants at the conference also got to try some of these activities with props that simulated wounds and responded favorably to the fresh resources.